2021
DOI: 10.3390/nano12010073
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensor for Methamphetamine Detection Using Laser-Induced Porous Graphene Electrode

Abstract: A 3D porous graphene structure was directly induced by CO2 laser from the surface of Kapton tape (carbon source) supported by polyethylene terephthalate (PET) laminating film. A highly flexible laser-induced porous graphene (LI-PGr) electrode was then fabricated via a facile one-step method without reagent and solvent in a procedure that required no stencil mask. The method makes pattern design easy, and production cost-effective and scalable. We investigated the performance of the LI-PGr electrode for the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The portable devices (with one or more potentiostats within) were sourced from PalmSens (Houten, The Netherlands). Their sizes are conveniently small enough that other researchers have also used them or adapted them for constructing portable electrochemical devices for the sensing and analysis of illicit drugs [ 51 , 52 ]. They can be interfaced with computers and mobile phones or tablets easily, enabling facile data processing and analysis.…”
Section: Sensing Using Commercially Available Carbon Screen-printed E...mentioning
confidence: 99%
See 1 more Smart Citation
“…The portable devices (with one or more potentiostats within) were sourced from PalmSens (Houten, The Netherlands). Their sizes are conveniently small enough that other researchers have also used them or adapted them for constructing portable electrochemical devices for the sensing and analysis of illicit drugs [ 51 , 52 ]. They can be interfaced with computers and mobile phones or tablets easily, enabling facile data processing and analysis.…”
Section: Sensing Using Commercially Available Carbon Screen-printed E...mentioning
confidence: 99%
“…A group in Thailand found a simple and very economical way to make a portable electrochemical sensor for methamphetamine [ 52 ]. It has been known that polyimide films, even commercial ones, can be turned into porous graphene structures, which were found to be excellent electrical conductors with a very large and specific surface area [ 55 ].…”
Section: Sensing Using Lab-fabricated or Modified Spe/spe-like Electr...mentioning
confidence: 99%
“…184 In addition, a fast and simple assay for in situ measurement of salivary thiocyanate ions was presented using a colorimetric paper-based sensing platform. 180 The developed paper-based sensing platform was based on a colored complexation reaction between iron (III) and thiocyanate under acidic conditions and a scanner was employed as a detection device for image analysis. The proposed method showed the LOD of thiocyanate as 0.06 mM at the optimal conditions and was also applied to measure thiocyanate in human saliva samples.…”
Section: Albumin and Kallikreinmentioning
confidence: 99%
“…To investigate selectivity, they tested the sensor's response versus sugars, salts (cations and anions), uric acid, urea and ascorbic acid, and they reported a highly selective response for methamphetamine (Figure 5). Regarding the real samples, they tested the sensor with saliva and household surfaces (sample recovered from glass, stainless steel and plastic surfaces), where they suggested that the satisfactory recovery results of testing real samples can indicate that their sensor has the potential to be applied in forensic investigations [93].…”
Section: Methamphetaminementioning
confidence: 99%